Psychological Characteristics Of Successful Women Entrepreneurs: A Case Study Of 2 Years Exit Programme - Fuad, Nurwahida (2023)
The main objective of this study is to examine the relationship between psychological characteristics and women's entrepreneurial success. The addition of three new variables—psychological women's empowerment, social competence, and entrepreneur resilience—expands the model of psychological characteristics.